2023
DOI: 10.3390/biom13020314
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Circular RNAs in the Development of Skeletal Muscle and Adipose Tissues of Farm Animals

Abstract: Circular RNAs (circRNAs) are a highly conserved and specifically expressed novel class of covalently closed non-coding RNAs. CircRNAs can function as miRNA sponges, protein scaffolds, and regulatory factors, and play various roles in development and other biological processes in mammals. With the rapid development of high-throughput sequencing technology, thousands of circRNAs have been discovered in farm animals; some reportedly play vital roles in skeletal muscle and adipose development. These are critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…The Tumor Immune Estimation Resource (TIMER) database is a comprehensive resource that systematically analyzes immune infiltrates in various cancer types. [ 29 ] Therefore, we used the TIMER database to examine the relationship between GDF15 and various immune cell types in liver cancer. These results demonstrate a negative correlation between GDF15 expression in HCC and the presence of CD8 + T cells, NK cells, and M1 macrophages (Figure S9A–C, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The Tumor Immune Estimation Resource (TIMER) database is a comprehensive resource that systematically analyzes immune infiltrates in various cancer types. [ 29 ] Therefore, we used the TIMER database to examine the relationship between GDF15 and various immune cell types in liver cancer. These results demonstrate a negative correlation between GDF15 expression in HCC and the presence of CD8 + T cells, NK cells, and M1 macrophages (Figure S9A–C, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The post-transcriptional regulation of gene expression is intricately governed by an ensemble of factors, including non-coding RNAs like miRNAs, circRNAs, and lncR-NAs [13]. These molecules exert their influence by modulating RNA stability, translation, and splicing, thereby contributing to the complex orchestration of biological processes in myogenesis [14][15][16][17][18]. Among this diverse landscape of post-transcriptional regulators, our particular focus centers on a distinct category: RNA-binding proteins (RBPs).…”
Section: Introductionmentioning
confidence: 99%
“…To date, emerging studies have suggested that non-coding RNAs affect skeletal muscle development by regulating gene expression, including microRNAs (miRNAs) [8], circular RNAs [9], and long non-coding RNAs (IncRNAs) [10]. Notably, miRNAs are a class of conserved small single-stranded RNAs that do not encode protein [11].…”
Section: Introductionmentioning
confidence: 99%